2018
DOI: 10.1177/0031512518764494
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Conditioning Activities on 100-m Dash Performance in High School Track and Field Athletes

Abstract: This study compared the effects of different conditioning activities on the 100-m dash performance of 11 male, high school track and field athletes (mean age = 16.3; SD = 1.2 years). Participants performed a 100-m dash seven minutes after each of four randomized conditioning protocols, with each condition and 100-m dash separated by 3-10 days. The conditioning protocols were (a) control, no conditioning activity; (b) weighted plyometric, three sets of 10 repetitions of alternate leg bounding with additional lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…As demonstrated, eight out of 12 volunteers positively responded to the CA. This individualized response to BP protocol is in agreement with other studies 27,33 and can explain the small effect size observed in the current study (d = 0.4). To date, it is unclear why CA does not benefit some individuals.…”
Section: Discussionsupporting
confidence: 94%
“…As demonstrated, eight out of 12 volunteers positively responded to the CA. This individualized response to BP protocol is in agreement with other studies 27,33 and can explain the small effect size observed in the current study (d = 0.4). To date, it is unclear why CA does not benefit some individuals.…”
Section: Discussionsupporting
confidence: 94%
“…Burkett et al [5] reported that that performing one set of five box jumps with an addition of 10% bodyweight by holding dumbbells resulted in a greater CMJ height as compared to dynamic exercise, static stretching and no warm up. This finding was supported by more recent studies that also reported acute improvement in sprint times after performing alternate leg bounding with additional 10% of bodyweight [10,29]. Therefore, it would benefit athletes to perform loaded plyometric exercises during their pre-competition warm up.…”
Section: Introductionsupporting
confidence: 58%
“…Effective PAPE effects have been reported using different types of conditioning stimulus, such as high resistance loads [6,12,13] or jumping exercises [14]. Although it was previously emphasized that PAPE stimulus is more effective when it is biomechanically similar to the subsequent activity [15], studies using sprints as conditioning stimuli to enhance sprint performance are limited [16,17]. These studies showed that adults did not improve their 60-m sprint speed after 2 × 60 m sprints [16], whereas young male track and field athletes increased their speed in a 100 m sprint after 2 × 20 m resisted sprints, and not after the same sprints as conditioning without resistance [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was previously emphasized that PAPE stimulus is more effective when it is biomechanically similar to the subsequent activity [15], studies using sprints as conditioning stimuli to enhance sprint performance are limited [16,17]. These studies showed that adults did not improve their 60-m sprint speed after 2 × 60 m sprints [16], whereas young male track and field athletes increased their speed in a 100 m sprint after 2 × 20 m resisted sprints, and not after the same sprints as conditioning without resistance [17]. It seems therefore that the properties of the conditioning stimulus might be critical for the outcome of the study.…”
Section: Introductionmentioning
confidence: 99%